THE IMPLEMENTATION OF WRITING STRATEGY FOR IMPROVING STUDENTS’ WRITING SKILL AT THE FOURTH SEMESTER STUDENTS OF THE INTERNATIONAL BALI TOURISM INSTITUTE, DENPASAR – BALI IN ACADEMIC YEAR 2017/2018 - Utik Kuntariati; Putu Dian Yuliani Paramita; Kadek Ayu Ekasani (Institut Pariwisata dan Bisnis Internasional, 2018)
This study was aimed at knowing whether the final product of composition which is given detailed feedback (error correction) performs better than of that given global feedback. The accessible population of the study was the fourth semester students of D3 tourism of The International Bali Tourism Institute, academic year 2017/2018. The study used quasi-experimental, nonrandomized control group, pretest-posttest design. This was so because the experiment was conducted in classroom setting in which the classes had been organized into classes A and B. The result of the study revealed that there was no significant difference of the two groups – experimental and control group. The result showed that the two groups had the same ability in writing paragraph. From the result concluded that the final product of composition written by students which is given detailed feedback (error correction) perform the same as of those given global feedback.